Does Oral Language Influence How First Graders Solve Arithmetic Word Problems? - Mancl, Lacey (My University, 2011)
This study aimed to 1) code a new portion of the existing data set and test statistically if group differences exist in first graders' flexibility in selecting solution strategies while solving traditionally-worded problems and 2) to re-code the scaffolding condition data set and test statistically if, when gesture and rewording scaffolds are presented, children with low oral language skill select different solution strategies than when traditionally-worded problems are presented.
Color poster with text, images, and graphs.
Keywords: Word problems (Mathematics)--Study and teaching (Elementary); Verbal ability in children--Educational aspects; Mathematical ability in children; Posters